Low Molecular Weight Heparin Improves the Inflammatory State of Acute Sinusitis Rats Through Inhibiting the TLR4-MyD88-NF-κB Signaling Pathway - Wu, Tong; He, Sihan; Jiao, Zan; Liang, Xiang; Chen, Yu; Liu, Huow; Zhang, Yongq; He, GuangX (Frontiers in Pharmacology, 2021)
Background: Low molecular weight heparins (LMWH),a natural sulfated glycosaminoglycan with the affinity to proangio-genic factors, is produced by chemical or enzymatic depolymerization of unfractionatedheparin (UFH). It is known for its anticoagulant effects. Recently, LMWH has been reported to have a strong anti-inflammatory effect in various kinds of inflammation, such as colitis, myocarditis, and airway inflammation. However, acting as a newly-developed anti-inflammatory drug, its anti-inflammatory mechanism was rarely studied. Methods:SD rats were randomly divided into control and experimental groups. The experimental group was established by building an acute nasal sinusitis model with expansion sponges mixed with Streptococcus pneumoniae.Then the experimental group rats were subcutaneously injected with different concentrations of LMWH.After seven consecutive days of injection,some rats were sacrificed,and then blood and nasal mucosa samples were taken to determine their inflammation status.The remaining acute sinusitis rats were randomly selected for a week of nasal irrigation with normal saline or saline mixed with different concentrations of LMWH.One week later, rats were sacrificed,and blood and nasal mucosa samples were taken to detect the inflammation status. Results:Rat nasal mucosa in the model group had obvious inflammation,and the degree of nasal mucosa inflammation damage in the experimental group was lower than in the experimental control group,which proved that LMWH has a protective effect on nasal mucosa,and the effect has a correlation with the dose.Irrigation of the nose with saline mixed with LMWH can improve the anti-inflammatory effect.Protein related to the TLR4-MyD88-NF-κB signaling path way was activated in the acute sinusitis rat model.LMWH can significantly inhibit its expression. Conclusion: We reported for the first time the anti-inflammatory effect of LMWH in acute upper respiratory tract. We studied its anti-inflammatory mechanism, too.And these findings may be the potential theoretical basis for its anti-tumor effect.